PELATIHAN PENERAPAN SISTEM INFORMASI MANAJEMEN SEKOLAH UNTUK MENINGKATKAN LAYANAN PENDIDIKAN DI ERA DIGITAL PADA SEKOLAH SMK NEGERI 1 BATUI SELATAN KECAMATAN BATUI KABUPATEN BANGGAI - Rahman, Wahyudin; Hadiyati, Rini; Saudin, La; Belani, Sriwanti (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This community service activity aimed to enhance the capacity of school staff in managing academic and financial data through the use of a School Management Information System (SIMS). The training included pre-test and post-test assessments to evaluate participants' understanding, participant satisfaction surveys, and practical exercises to apply the system. Results indicated a 35% improvement in participants’ knowledge, as reflected in the post-test scores. The satisfaction survey showed that 85% of participants were satisfied with the training material and delivery, though some participants still required additional support in using more advanced features of the system. The training also helped improve the efficiency and transparency of school data management, particularly in academic and financial reporting. By incorporating digital solutions into school management, the training contributed to the overall improvement of educational services. This initiative serves as an example for other schools to implement technology-driven solutions to improve administrative processes.